2018
DOI: 10.1371/journal.ppat.1007237
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T cells mediate protection against Zika associated severe disease in a mouse model of infection

Abstract: Zika virus (ZIKV) has gained worldwide attention since it emerged, and a global effort is underway to understand the correlates of protection and develop diagnostics to identify rates of infection. As new therapeutics and vaccine approaches are evaluated in clinical trials, additional effort is focused on identifying the adaptive immune correlates of protection against ZIKV disease. To aid in this endeavor we have begun to dissect the role of CD4+T cells in the protection against neuroinvasive ZIKV disease. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(141 citation statements)
references
References 66 publications
(57 reference statements)
7
132
2
Order By: Relevance
“…Future studies will address the immune profiles of human ZIKV-specific CD4 + T cells and compare the functionalities of CD4 + T cells with the ones of CD8 + T cells. Indeed, recent studies in humans and mouse models have shown the importance of ZIKV-specific CD4 + T cells in protecting from severe ZIKV severe and Ab development (25)(26)(27). Additionally, it would be of interest to test whether disease severity during the acute phase impacts the gene transcription and protein expression in ZIKVspecific T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies will address the immune profiles of human ZIKV-specific CD4 + T cells and compare the functionalities of CD4 + T cells with the ones of CD8 + T cells. Indeed, recent studies in humans and mouse models have shown the importance of ZIKV-specific CD4 + T cells in protecting from severe ZIKV severe and Ab development (25)(26)(27). Additionally, it would be of interest to test whether disease severity during the acute phase impacts the gene transcription and protein expression in ZIKVspecific T cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the cytotoxic profile of the CD4+ T cells present 12 months after DENV infection and during heterologous ZIKV challenge correlate with better performance relative to the early (3 months) or late (2.5 years) (24) periods of time after the primary DENV infection. The role of CD4+T cells in flavivirus infection has been extensively documented (56) (57). Importantly, Weiskopf et al and others have also shown that DENV CD4+T cells are readily detectable early following DENV infection, and the frequency of DENV-specific CD107a+ CD4+T correlate with enhanced protection against DENV disease (58, 59) and play a key role in controlling secondary flavivirus infections (26).…”
Section: Discussionmentioning
confidence: 99%
“…The ZIKV strain PRVABC59 used was a kind gift of Robert Lanciotti (CDC). The ZIKV used was grown in Vero cells from the American Type Culture Collection (ATCC CCL-81) and stored at −80 • C, as described previously [19,22,49]. The human serum samples were obtained from the University of North Carolina/ National Institute of Health (UNC/NIH) Traveler Study through BEI Resources, NIAID, NIH: human convalescent plasma.…”
Section: Viruses Human Serum and Cellsmentioning
confidence: 99%